2020
DOI: 10.1002/eat.23299
|View full text |Cite
|
Sign up to set email alerts
|

Sexual function and dysfunction among women with anorexia nervosa: A systematic scoping review

Abstract: Objective Research suggests that a variety of biological and psychosocial factors are associated with the sexual health of women diagnosed with anorexia nervosa (AN). This systematic scoping review, conducted in accordance to Preferred Reporting Items for Systematic Reviews and Meta‐Analyses Guidelines, synthesizes the current literature concerning sexual function and dysfunction in women with AN. Method We searched PubMed, EMBASE, and PsychInfo for literature published until April 2020. All study designs were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 77 publications
0
12
0
Order By: Relevance
“…The majority of our patients (107, 93.8%), who had no hypertension, had a median IIEF-5 score of 23 (20)(21)(22)(23)(24)(25), compared with patients (seven, 6.2%) with hypertension, who showed significantly lower IIEF-5 score, with a median of 15 (15-15) (p = 0.045). We also assessed whether the serum level of anti-transglutaminase antibodies had any influence on IIEF-5 score and found no correlation (data not shown).…”
Section: Sexual Function In Male Patientsmentioning
confidence: 68%
See 2 more Smart Citations
“…The majority of our patients (107, 93.8%), who had no hypertension, had a median IIEF-5 score of 23 (20)(21)(22)(23)(24)(25), compared with patients (seven, 6.2%) with hypertension, who showed significantly lower IIEF-5 score, with a median of 15 (15-15) (p = 0.045). We also assessed whether the serum level of anti-transglutaminase antibodies had any influence on IIEF-5 score and found no correlation (data not shown).…”
Section: Sexual Function In Male Patientsmentioning
confidence: 68%
“…Several evidence shows how BMI within normal limits is associated with better sexual function than obesity or excessive thinness. 24,25 Additionally, Wekker et al 26 showed that improving lifestyle in patients with obesity and infertility was associated, within 6 months, with increased sexual intercourse, improved vaginal lubrication as well as improved overall sexual function. On the other side, use of antianxiety or antidepressant drugs did not seem to be associated with altered sexual function in our female CD population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This likely stems from a combination of endocrine dysregulation as well as psychological factors. 42 A nutritionally adequate diet rich in whole foods and plants is supportive of health on multiple levels, including for promotion of optimal sexual function.…”
Section: Sexual Healthmentioning
confidence: 99%
“…Sexual dysfunction is common in patients with ED; nevertheless, there are few studies dedicated to this topic [ 15 ]. A scoping review failed to include any study related to sexual dysfunction in adolescent patients with AN [ 16 ]. This is noteworthy because ED often occur during puberty and adolescence, which are also sensitive periods for psychosexual development.…”
Section: Introductionmentioning
confidence: 99%